Dissemination of Milkfish Processing Sterilization Equipment to Improve Quality and Marketing Reach - Fibriana, Fidia; Martuti, Nana Kariada Tri; Sunyoto, Sunyoto; Saputro, Danang Dwi; Susilowati, Nurdian; Larasati, Dewi (Universitas Negeri Semarang, 2024)
Milkfish processing is a superior product and a typical souvenir from Semarang City that requires serious attention because it has a significant impact on regional economic growth. Tambakrejo Village is a thematic village of Semarang City (Milkfish Processing Village) with the formation of the Putri Laut Processing and Marketing Group (Poklahsar) since 2017 with 21 members. Business actors in Poklahsar still face problems in production and marketing aspects. Partners in this PDTI are Poklahsar Putri Laut and Tambakrejo Village. In terms of production, the production capacity of presto milkfish is limited to only ± 50 kg / day. In addition, processed milkfish has a short shelf life so that technology needs to be applied. The reach of marketing aspects, product promotion is still lacking , In this community service activity, Retort pan facilities were provided, is one of the thermal food preservation techniques, which has many advantages, namely a shelf life of more than six months. The pressure cooker is a hybrid model specifically designed to make soft-boned milkfish effectively and efficiently. This presto milkfish cooker is a combination of innovations about soft-boned milkfish cookers with temperature and time control . The tool still uses LPG fuel and a soft-boned milkfish cooker with an electric heater.